2014
DOI: 10.7860/jcdr/2014/6885.3960
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Manifestations of Dengue Fever – Where Do We Stand Today?

Abstract: Background and Objectives: Dengue fever (DF) is transmitted by Aedes aegypti mosquitoes. With growing population, rapid urbanization and lack of appropriate sanitary measures, prolifer ation of mosquitoes and subsequent dengue infections have increased rampantly with an estimated 30fold increase in incid ence over last five decades. With rising disease burden, atypical manifestations have increased as well, which are missed most often due to lack of awareness. Our aim was to look for the atypical manifestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
39
4
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 8 publications
5
39
4
3
Order By: Relevance
“…*P < 0.05 previous studies, the incidence of dengue-associated acute liver failure ranged from 0.66% to 0.77%. 4,7 Therefore, our study revealed a lower incidence than found in previous studies. In the present study, the incidence of acute liver failure among patients with dengue was 3.1/1,000 patients, which is higher than that found in a previous study in Vietnam (1.5/1,000 patients with dengue).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…*P < 0.05 previous studies, the incidence of dengue-associated acute liver failure ranged from 0.66% to 0.77%. 4,7 Therefore, our study revealed a lower incidence than found in previous studies. In the present study, the incidence of acute liver failure among patients with dengue was 3.1/1,000 patients, which is higher than that found in a previous study in Vietnam (1.5/1,000 patients with dengue).…”
Section: Discussioncontrasting
confidence: 63%
“…Acute liver failure secondary to dengue is rare but has a high mortality rate. 4 Acute liver failure is defined as the rapid onset of acute encephalopathy and coagulopathy in a patient without preexisting cirrhosis and with < 26-week duration of illness. 5,6 Severe hepatic involvement (acute liver failure) is a rare condition in patients with dengue, but commonly occurs during the second week of illness.…”
Section: Introductionmentioning
confidence: 99%
“…However, when calculated for more than 3 times of normal for 47.5% raised ALT and 77.2% had raised AST. In a study by Nimmaggada et al (9) it was shown that raised liver enzymes were seen in 92.6% of cases. Overall, 92.7% of patients had Aspartate Transaminase (AST) > 40 U/L and three-fold increase was seen in 58.7%.…”
mentioning
confidence: 93%
“…La frecuencia de compromiso de órganos encontrada fue de 18.1%, similar a la descrita en la serie de Salgado et al (7), constituyéndose en la segunda causa de DG, después del choque. La miocarditis, con 14 casos, ocupó el primer lugar dentro de las causas de organopatía, resaltando la importancia de su diagnóstico en dengue (7,14,15).…”
Section: Discussionunclassified